Illumination-Independent Reflectance Information Acquirement for Leaf Water Potential Measurement on the Example of Satsuma Mandarin - Kriston-Vizi, J.; Umeda, M.; Miyamoto, K.; Ferenczy, A. (International Journal of Horticultural Science, 2003)
Mandarin fruit sugar content can be increased when subjecting the satsuma mandarin tree (Citrus unshiu MARC. var. satsuma) to moderate water stress by mulching during the period of active sugar accumulation, thereby fruit quality improvement can be realized. In the frame of the precision agriculture production system, a non-destructive measuring method development became necessary based on remote sensing, field spectroscopy and image analysis, to be able to measure the degree of water stress. Large amount of visual information have been recorded at ground level, in near infrared, red and green channels by a false color digital camcorder designed specially for remote sensing applications. A method have been found to be able to calculate the absolute reflection of mandarin leaf surface by comparing leaf reflectance with known reference target reflectance, thereby established the basis of further studies in this topic. Leaf absolute reflection can be measured reliably, under variable natural illumination at field conditions. Functional correlation can be searched between visual information and leaf water potential measured by PMS pressure chamber.